Integration of Puppet Story Cultural Values in Strengthening the Character of Elementary School Students - Nuryanti, Nuryanti; Slamet, St. Y.; Daryanto, Joko (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
This study aims to analyze the form of integration of the cultural value of wayang stories in Indonesian learning in elementary schools, describe the perception of teachers and students of the character values contained in the puppet story, and identify the challenges of its implementation as a character strengthening strategy. The research uses a descriptive qualitative approach with a staked case study design focused on grade IV of SDN 1 Tawangharjo involving 1 classroom teacher and 25 fourth-grade students as research subjects. Data was collected through in-depth interviews, participant observations, and documentation, and analyzed using thematic-interactive analysis techniques with data triangulation. The results of the study show that wayang stories are used contextually in the planning and implementation of learning that contains character values such as responsibility, courage, and mutual cooperation. Teachers develop thematic modules based on local stories, but still face obstacles in the formulation of value indicators, limitations in visual media, and students' symbolic understanding. The implications of these findings underscore the need to develop a curriculum based on local culture, value literacy training for teachers, and continuous evaluation of students' character. This research contributes significantly to strengthening culturally and contextually relevant character learning in elementary schools by providing a practical framework for integrating local cultural values into formal education curricula.